2015
DOI: 10.1161/strokeaha.115.009643
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acute Lesion Topography in Initial Ischemic Stroke Severity and Long-Term Functional Outcomes

Abstract: Background and Purpose Acute infarct volume, often proposed as a biomarker for evaluating novel interventions for acute ischemic stroke (AIS), correlates only moderately with traditional clinical endpoints such as the modified Rankin Scale (mRS). We hypothesized that the topography of acute stroke lesions on diffusion-weighted MRI (DWI) may provide further information with regard to presenting stroke severity and long-term functional outcomes. Methods Data from a prospective stroke repository were limited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 24 publications
16
125
2
1
Order By: Relevance
“…This result is in agreement with the recent data from Wu et al, 37 who showed using VLSM maps on mRS that several locations highlighted as eloquent are no longer significant after accounting for age and stroke volume. This suggests that the impact of stroke location is decreased if other established predictors are considered.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is in agreement with the recent data from Wu et al, 37 who showed using VLSM maps on mRS that several locations highlighted as eloquent are no longer significant after accounting for age and stroke volume. This suggests that the impact of stroke location is decreased if other established predictors are considered.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that the impact of stroke location is decreased if other established predictors are considered. Furthermore, Wu et al 37 did not include initial NIHSS as a covariate. Nevertheless, NIHSS has clearly emerged as an independent predictor and is usually recommended in core outcome predictive model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research emphasized the importance of lesion topography in initial stroke severity and long-term functional outcome rather than simple ischemic lesion volume or pattern. 31 Authors speculate that the discrepancy between ischemic lesion pattern and functional outcome in this study, at least in part, could be explain by the role of lesion topography on clinical outcome in patients with acute ischemic stroke.…”
Section: Strokementioning
confidence: 56%
“…1,22 Interestingly, small vessel stroke subtype was not associated with mRS score, which is likely a consequence of insufficient power of this portion of the analysis (n 5 29 patients with stroke attributed to small vessel occlusion), or alternatively, it is suggestive of a complex relationship between clinical outcome and stroke subtype, which may involve additional variables such as interaction with stroke lesion topography. 18 Overall, the role of WM microstructural integrity in the acute ischemic tissue outcomes warrants further investigation.…”
Section: Resultsmentioning
confidence: 98%
“…Compared to the larger institutional dataset of AIS patients with brain MRI on admission, there was no significant difference in age, admission stroke severity, distribution of the TOAST subtypes, nWMHv, or poststroke mRS score (data not shown). 18 In univariable analysis, hypertension (b 5 (table 2). There was no association between the metrics of diffusivity anisotropy and acute infarct volume.…”
Section: Resultsmentioning
confidence: 99%